Spindle epithelial tumor with thymus‐like differentiation: A case report and comprehensive review of the literature and treatment options. Issue 5 (5th May 2014) - Recondo, Gonzalo; Busaidy, Naifa; Erasmus, Jeremy; Williams, Michelle D.; Johnson, Faye M.
Abstract: Background: Spindle epithelial tumor with thymus‐like differentiation (SETTLE) is a rare cancer of thymic origin with little information available for treating clinicians. Methods: We performed a comprehensive literature search and updates were requested from all authors. We report one recent case. Results: We present the most comprehensive review of the clinical literature for SETTLE. We identified 41 published cases. SETTLE usually presents as an asymptomatic neck mass. Most patients successfully underwent surgical resection of the primary tumor. The mean latency to develop metastasis was 10 years. SETTLE is uniformly responsive to radiotherapy and combination chemotherapy in the rare cases where response data are available. Conclusion: Although SETTLE is initially indolent, it has the capacity to metastasize late in its course. The malignant potential of this tumor might be underestimated because of the lack of long‐term follow‐up. In cases in which complete surgical resection is not possible, radiotherapy or combination chemotherapy is effective. © 2014 Wiley Periodicals, Inc. Head Neck 37: 746–754, 2015